Cognitive performance is lower among individuals with overlap syndrome than in individuals with COPD or obstructive sleep apnea alone: association with carotid artery stiffness - Luehrs, Rachel E. (J Appl Physiol (1985), 2021)
Chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA) are both independently associated with increased cardiovascular disease (CVD) risk and impaired cognitive function. It is unknown if individuals with both COPD and OSA (i.e., overlap syndrome) have greater common carotid artery (CCA) stiffness, an independent predictor of CVD risk, and lower cognitive performance than either COPD or OSA alone. Elevated CCA stiffness is associated with cognitive impairment in former smokers with and without COPD in past studies. We compared CCA stiffness and cognitive performance between former smokers with overlap syndrome, COPD only, OSA only and former smoker controls using analysis of covariance (ANCOVA) tests to adjust for age, sex, body mass index (BMI), pack years, and postbronchodilator FEV(1)/FVC. We also examined the association between CCA stiffness and cognitive performance among each group separately. Individuals with overlap syndrome (n = 12) had greater CCA β-stiffness index (P = 0.015) and lower executive function-processing speed (P = 0.019) than individuals with COPD alone (n = 47), OSA alone (n = 9), and former smoker controls (n = 21), differences that remained significant after adjusting for age, BMI, sex, pack years, and FEV(1)/FVC. Higher CCA β-stiffness index was associated with lower executive function-processing speed in individuals with overlap syndrome (r = −0.58, P = 0.047). These data suggest that CCA stiffness is greater and cognitive performance is lower among individuals with overlap syndrome compared with individuals with COPD or OSA alone and that CCA stiffening may be an underlying mechanism contributing to the lower cognitive performance observed in patients with overlap syndrome. NEW & NOTEWORTHY Previous studies have demonstrated greater carotid artery stiffness and lower cognitive function among individuals with COPD alone and OSA alone. However, the present study is the first to demonstrate that individuals that have both COPD and OSA (i.e., overlap syndrome) have greater carotid artery stiffness and lower executive function-processing speed than individuals with either disorder alone. Furthermore, among individuals with overlap syndrome greater carotid artery stiffness is associated with lower executive function-processing speed.